Socio-Ecological Resilience of Coastal Communities in Indramayu Integrating Population Dynamics, Environmental Behavior, and Local Capacity - Rizkiyah, Wiji Febriani (Gema Wiralodra, 2025)
The coastal region of Indramayu Regency faces complex socio-ecological pressures resulting from the interaction between population growth, environmental degradation, and limited human capacity. This study aims to analyze the interrelationship between population dynamics, environmental conditions, and the role of Population and Environmental Education (PKLH) in strengthening the socio-ecological resilience of coastal communities. The research employs a descriptive qualitative approach using a case study design based on secondary data, including the Indramayu Regency Regional Statistics 2024 publication, previous research articles, policy documents, and theoretical literature. Thematic analysis was carried out using the writing-as-inquiry principle and theoretical triangulation to ensure interpretive depth. Findings reveal that high population growth, educational disparities, and economic dependence on the agriculture–fisheries sector have intensified pressure on coastal ecosystems, particularly through abrasion, seawater intrusion, and fishpond land conversion. On the other hand, various local initiatives based on environmental education and social wisdom—such as mangrove restoration in Karangsong and educational tourism management in Juntinyuat—indicate a shift in community ecological behavior from dependence to awareness. Through the Population–Environment–PKLH Nexus framework, this research confirms that population and environmental education act as mediators transforming knowledge into awareness and collective ecological action. The study recommends repositioning coastal development policy from a physical approach to a participatory socio-ecological approach. The resilience of Indramayu’s coastal communities depends not only on infrastructure but also on the degree to which PKLH values are internalized in their social life.